"Drunk up by thirsty nothing": The Fissured World of Prometheus Unbound. Issue 1 (1st January 2015) - Garofalo, Devin M.
Abstract : Taking Percy Bysshe Shelley's Prometheus Unbound as its point of departure, this essay investigates the unsettled interrelationship between the forms of poetry and world in the Romantic period, and the implications it bears for the formalisms employed by scholars of Romanticism. I argue that poetic form is inextricable from systems of world-organization in the period, the former internalizing, subverting or even transforming the latter. Deploying an iterative model of poetic form whose structures imperfectly echo one another, Shelley envisions the world as constituted by "intervals" and "interstices., " Emanating most immediately from Demogorgon's "formless" and yet formative figure, these fissures proliferate unruly slippages and gaps that undo the perfectly repetitious, totalizing and enclosed edifice of Jupiterian empire. In so doing, the iterative forms of Prometheus Unbound make way for a more heterogeneous and loving world-order to take hold, both upon the sociopolitical organizations of man and the uniform "ruin upon ruin" emblazoned in the gaping depths of earth.